(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
Gender inequality is one of the most pervasive forms of inequality in the world. This is not just because, it is present in most societies, but also because; it cuts across other forms of inequalities in human endeavour. This paper shows that, the geography of gender inequality reflects systematic regional differences in institutions of Kinship and family, the household patterns they have given rise to and the associated gender division of resources and responsibilities. Thus, a great deal of human behaviour is not the result of individual preferences. Rather, it is governed by institutional rules, norms and conventions that have powerful material effects in people’s lives. These rules may be written or unwritten, explicit or implicit, statutory or non-statutory, but sanctified by religion, upheld by convention or embodied in the standards of family, community and society